Identification and description of controlled clinical trials in Spanish language dental journals. (10th April 2018) - Villanueva, Julio; Delgado, Isabel; Saldarriaga, Julio R.; Gargallo, Maria Garcia; Amaro, Yanina; Zapata, Sebastián; Núñez, Lorena; Zamorano, Gabriel; Pardo‐Hernandez, Hector; Bonfill, Xavier; Martin, Conchita
Abstract: Background: To identify controlled clinical trials (CCTs) published in Spanish and in Latin American dental journals, and provide access to this body of evidence in a single source. Methods: Handsearching, following Cochrane Collaboration guidelines, of CCTs published in Spanish dental journals from Spain and Latin America. For each eligible trial, we collected the dental specialty, the interventions evaluated, whether and how randomisation was achieved, and the corresponding bibliographic reference. Results: We handsearched 107 journals published in Spain and Latin America in Spanish. Over 17 051 articles, 244 (1.43%) were CCTs. These studies focused mainly on periodontics (70, 29.0%) and oral and maxillofacial surgery (66, 27.0%), assessing mostly pharmacological interventions (112, 46.0%). One hundred fifty‐three studies (62.7%) used a random allocation of participants to study arms. Conclusions: A significant number of dental journals published in Spain and Latin America in Spanish language present original research relevant to inform clinical practice. These journals are not indexed in the major electronic databases. Practical Implications: References to the identified CCTs are now available in CENTRAL, the Cochrane Collaboration repository for these studies. We call for adherence to the CONSORT statement in dentistry to improve reporting of CCTs in journals published in Spanish language.